Research progress of neuroimaging of blood-brain barrier breakdown in Alzheimer's disease patients - Qin XU; Feng BAI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2017)
Recent studies indicate that blood-brain barrier (BBB) breakdown may play an important role in the pathophysiology of cognitive dysfunction and dementia. BBB regulates the homeostasis of brain microenvironment, controls the transfer of required nutrients (e.g., glucose and amino acids), and limits entry of blood - derived products, pathogens and neurotoxins into the brain tissue. Recent advances in neuroimaging techniques offer new possibilities to realize positioning and quantitative detection of BBB disruption. It provides a new insertion point for elucidating the pathogenesis of Alzheimer's disease (AD).   DOI: 10.3969/j.issn.1672-6731.2017.06.013